Research progress on the synthesis and pharmacology of 1,3,4-oxadiazole and 1,2,4-oxadiazole derivatives: a mini review - Wang, Jing-Jing; Sun, Wen; Jia, Wei-Dong; Bian, Ming; Yu, Li-Jun (Journal of enzyme inhibition and medicinal chemistry, 2022)
Oxadiazole is a five-membered heterocyclic compound containing two nitrogen atoms and one oxygen atom. The 1,3,4-oxadiazole and 1,2,4-oxadiazole have favourable physical, chemical, and pharmacokinetic properties, which significantly increase their pharmacological activity via hydrogen bond interactions with biomacromolecules. In recent years, oxadiazole has been demonstrated to be the biologically active unit in a number of compounds. Oxadiazole derivatives exhibit antibacterial, anti-inflammatory, anti-tuberculous, anti-fungal, anti-diabetic and anticancer activities. In this paper, we report a series of compounds containing oxadiazole rings that have been published in the last three years only (2020-2022) as there was no report or their activities described in any article in 2019, which will be useful to scientists in research fields of organic synthesis, medicinal chemistry, and pharmacology.